SECURITY ANALYSIS IN IOT TECHNOLOGIES - Berdimurodov Mansur; Babajanov Mumin; Farmonov Bobur (Web of Journals Publishing, 2025)
Internet of Things (IoT) technologies are becoming an integral part of our daily lives. IoT systems work efficiently through interconnected devices, but these connections also lead to several security risks. This paper analyzes the specific methods and technologies used to ensure security in IoT systems. It examines how the protection of IoT devices is implemented in a changing environment, and how cryptography and authentication methods work to ensure network security and data protection. The research also explores advanced technologies aimed at reducing risks and threats in IoT systems.
Keywords: IoT, security, authentication, cryptography, network security, protection methods, device security.